The Role of Cadres in the Implementation of Posyandu Activities in Pudun Jae Lk I Village, Batunadua Health Center Working Area, Padangsidimpu City, in 2025 - Putri, Yolanda; Meilani Harahap; Darma Afni Hasibuan; Rahmi Wahida Siregar; Seri Hafni; Layla Fadhilah Rangkuti (PT Inovasi Pratama Internasional, 2025)
The Integrated Health Service Post (Pos Pelayanan Terpadu), better known as POSYANDU, serves as a means for community health empowerment because its implementation model is activated and initiated by the community, aligned with their respective needs. The role of cadres (health volunteers) in organizing Posyandu is crucial, as they are not only providers of health information to the community but also community mobilizers, encouraging people to visit the Posyandu and adopt clean and healthy living behaviors. The objective of this study was to determine the role of cadres in the implementation of Posyandu activities in Pudun Jae Lk I Village, within the working area of the Batunadua Health Center, Padangsidimpuan City, in 2025. This study used a descriptive qualitative method. There were 10 informants in this study, consisting of 4 mothers with toddlers, 4 Posyandu cadres, 1 health worker, and 1 Posyandu leader. Data analysis was conducted using qualitative descriptive methods, and data validity was ensured through data triangulation. The study results indicated that cadres had not yet fulfilled their roles in managing malnutrition among toddlers. Obstacles faced by the cadres included a lack of knowledge about Posyandu, particularly concerning malnutrition, due to a lack of training. The conclusion of this study is that the role of cadres in implementing Posyandu activities in Pudun Jae Lk I Village, Batunadua Health Center working area, Padangsidimpuan City, has not been carried out optimally. It is recommended that Posyandu cadres and officers enhance the knowledge and skills of cadres, particularly in toddler nutrition, and improve counseling programs for mothers regarding Posyandu and its benefits for mothers and toddlers